2005
DOI: 10.4049/jimmunol.175.7.4697
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-Mediated Inhibition of Cyclic Nucleotide Phosphodiesterase Activity and Expression Suppresses TNF-α and IL-1β Production in Monocytes by Elevation of Guanosine 3′,5′-Cyclic Monophosphate

Abstract: The trace element zinc affects several aspects of immune function, such as the release of proinflammatory cytokines from monocytes. We investigated the role of cyclic nucleotide signaling in zinc inhibition of LPS-induced TNF-α and IL-1β release from primary human monocytes and the monocytic cell line Mono Mac1. Zinc reversibly inhibited enzyme activity of phosphodiesterase-1 (PDE-1), PDE-3, and PDE-4 in cellular lysate. It additionally reduced mRNA expression of PDE-1C, PDE-4A, and PDE-4B in intact cells. Alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
117
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 143 publications
(126 citation statements)
references
References 46 publications
7
117
2
Order By: Relevance
“…On the other hand, there was only IL-1β release on behave of LPS+INFγ BMDM and treatment with cGMP analogue significantly decreased the production of IL-1β in this M1 population. In agreement with this results, inhibiting PDE activity in human monocytes decreased the release of IL-1β and this effect was mimic by cGMP analogues and NO donor suggesting NO-GC activation is implied in the effect (von Bulow et al 2005). Taking these results together suggest that increase cGMP levels promoted by sildenafil affect inflammatory outcomes, do not significantly reverse M1 phenotype but it does promote M2 phenotype and anti-inflammatory mediators.…”
Section: Discussionsupporting
confidence: 78%
“…On the other hand, there was only IL-1β release on behave of LPS+INFγ BMDM and treatment with cGMP analogue significantly decreased the production of IL-1β in this M1 population. In agreement with this results, inhibiting PDE activity in human monocytes decreased the release of IL-1β and this effect was mimic by cGMP analogues and NO donor suggesting NO-GC activation is implied in the effect (von Bulow et al 2005). Taking these results together suggest that increase cGMP levels promoted by sildenafil affect inflammatory outcomes, do not significantly reverse M1 phenotype but it does promote M2 phenotype and anti-inflammatory mediators.…”
Section: Discussionsupporting
confidence: 78%
“…One major group of genes affected by zinc status is related to inflammation, and zinc can directly affect several kinds of inflammatory diseases, including rheumatoid arthritis, diabetes, asthma, and sepsis (6)(7)(8)(9)(10)(12)(13)(14). Another interesting aspect of zinc status is found in elderly individuals, who in general show a significant reduction of their plasma or serum zinc levels.…”
Section: Discussionmentioning
confidence: 97%
“…However, zinc supplementation also entails the possibility of unwanted side effects. The production of proinflammatory cytokines by monocytes is antagonized by an inhibition of phosphodiesterases by zinc (12). Accordingly, zinc can suppress proinflammatory cytokine release during sepsis in in vivo models, but on the other hand, it can also worsen the symptoms (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, some previous reports have already suggested that zinc exerts modulatory effects on the immune system 14. Specifically, zinc can induce monocytes to differentiate to macrophages,24 and 100 × 10 −6 m zinc can increase the release of pro‐inflammatory cytokines such as IL‐1, IL‐6, and TNF‐α; however, 1.25 × 10 −6 m zinc is enough to decrease the expression of pro‐inflammatory cytokines 25. The immunomodulatory effect of zinc seems to be dose dependent.…”
Section: Discussionmentioning
confidence: 99%